Laminin and Matrix metalloproteinase 11 regulate Fibronectin levels in the zebrafish myotendinous junction - Jenkins, Molly H. (Skelet Muscle, 2016)
BACKGROUND: Remodeling of the extracellular matrix (ECM) regulates cell adhesion as well as signaling between cells and their microenvironment. Despite the importance of tightly regulated ECM remodeling for normal muscle development and function, mechanisms underlying ECM remodeling in vivo remain elusive. One excellent paradigm in which to study ECM remodeling in vivo is morphogenesis of the myotendinous junction (MTJ) during zebrafish skeletal muscle development. During MTJ development, there are dramatic shifts in the primary components comprising the MTJ matrix. One such shift involves the replacement of Fibronectin (Fn)-rich matrix, which is essential for both somite and early muscle development, with laminin-rich matrix essential for normal function of the myotome. Here, we investigate the mechanism underlying this transition. RESULTS: We show that laminin polymerization indirectly promotes Fn downregulation at the MTJ, via a matrix metalloproteinase 11 (Mmp11)-dependent mechanism. Laminin deposition and organization is required for localization of Mmp11 to the MTJ, where Mmp11 is both necessary and sufficient for Fn downregulation in vivo. Furthermore, reduction of residual Mmp11 in laminin mutants promotes a Fn-rich MTJ that partially rescues skeletal muscle architecture. CONCLUSIONS: These results identify a mechanism for Fn downregulation at the MTJ, highlight crosstalk between laminin and Fn, and identify a new in vivo function for Mmp11. Taken together, our data demonstrate a novel signaling pathway mediating Fn downregulation. Our data revealing new regulatory mechanisms that guide ECM remodeling during morphogenesis in vivo may inform pathological conditions in which Fn is dysregulated.